PENERAPAN ANALISIS SWOT DALAM MENENTUKAN STRATEGI PEMASARAN PADA RAMAYANA, ALUN-ALUN KOTA MALANG (STUDI PADA RAMAYANA ALUN-ALUN KOTA MALANG) - Retno Ayu Dewi Novitawati (Universitas Islam Bandung, 2022)
Distributing products, both goods and services to consumers' hands to meet consumer needs and desires, is one of the important roles of marketing. The existence of a company needs to be analyzed to determine the company's environmental conditions both internally which includes strengths and weaknesses, and externally including opportunities and threats. The purpose of this study was to determine the application of SWOT analysis in determining marketing strategies at Ramayana Alun-Alun Malang.The type of research approach carried out in this study is through a qualitative descriptive approach. Data collection techniques in this study were through observation, interviews, questionnaires, and documentation. Analysis of the data used in this study is to use analysis, IFAS, EFAS and SWOT. The results of the study show that the Ramayana Alun-Alun Kota Malang internally has a competitive strategy and is fairly strong. Externally Ramayana can take advantage of all opportunities well to avoid threats. Based on the SWOT matrix, Ramayana Alun-Alun Kota Malang supports an aggressive growth policy.